Politics, Parties, People: Field Notes from Electoral Campaigns in Odisha|India - Sriranjan, Priti; Jena, Bikram Keshori (Issues in Social Science, 2024)
This report is about a critical analysis of elections in Odisha over the past few decades. Diverse social groups in the state have been politicised and mobilised for electoral purposes based on social cleavages, rather than common economic interest, ideology or leadership. A theoretical framework has been developed in almost every district to analyse and trace the processes of tradition and reconfiguration of the electoral landscape. It answers the questions: What message does the state hold for Parliament or assembly elections? How do the people, who belong to a state, respond to national and state leaderships? Our state has been receiving appreciation as a platform where mainstream politics unfolds and, in a significant way, shapes the national politics including the formation and stability of the government at the Centre, a trend that started in the post-Congress polity. But it may raise a lot of questions among the political pundits and strategic gurus about how the new style of election mechanism and campaign approach should be re-looked. “Naveen Raj” continues in Odisha with chief minister Naveen Patnaik’s unmatched leadership not only registering successive wins in elections but also touching minds and hearts. My paper does not waste so many words on the defeat the Congress, India’s oldest political party, in successive elections in the state. It does not also focus much on the Bharatiya Janata Party, which has been not accepted by people in Odisha despite changing election slogans from ‘vikash’ (development) to ‘kabastan’ (burial ground) and ‘Pakistan’ from one election to another. My paper attempts to study how leadership and style of approach in electoral politics causes landslide wins for Patnaik and the Biju Janata Dal. In 2019 general and state assembly elections, the Congress was on the backfoot from day one. The fight in Odisha was directly between Prime Minister Narendra Modi and chief minister Patnaik. The first was known for his outstanding skill of 5P (passion, propaganda, promotion, publicity and progressiveness) and the second for his 3D effect (decency, discipline and difference). I will, however, also take look at lack of 3I (infrastructure, identity and ideology) in the electoral process.